PNPLA3 has retinyl-palmitate lipase activity in human hepatic stellate cells. (25th March 2014) - Pirazzi, Carlo; Valenti, Luca; Motta, Benedetta Maria; Pingitore, Piero; Hedfalk, Kristina; Mancina, Rosellina Margherita; Burza, Maria Antonella; Indiveri, Cesare; Ferro, Yvelise; Montalcini, Tiziana; Maglio, Cristina; Dongiovanni, Paola; et al.
Abstract : Retinoids are micronutrients that are stored as retinyl esters in the retina and hepatic stellate cells (HSCs). HSCs are key players in fibrogenesis in chronic liver diseases. The enzyme responsible for hydrolysis and release of retinyl esters from HSCs is unknown and the relationship between retinoid metabolism and liver disease remains unclear. We hypothesize that the patatin-like phospholipase domain-containing 3 (PNPLA3) protein is involved in retinol metabolism in HSCs. We tested our hypothesis both in primary human HSCs and in a human cohort of subjects with non-alcoholic fatty liver disease ( N = 146). Here we show that PNPLA3 is highly expressed in human HSCs. Its expression is regulated by retinol availability and insulin, and increased PNPLA3 expression results in reduced lipid droplet content. PNPLA3 promotes extracellular release of retinol from HSCs in response to insulin. We also show that purified wild-type PNPLA3 hydrolyzes retinyl palmitate into retinol and palmitic acid. Conversely, this enzymatic activity is markedly reduced with purified PNPLA3 148M, a common mutation robustly associated with liver fibrosis and hepatocellular carcinoma development. We also find the PNPLA3 I148M genotype to be an independent ( P = 0.009 in a multivariate analysis) determinant of circulating retinol-binding protein 4, a reliable proxy for retinol levels in humans. This study identifies PNPLA3 as a lipase responsible for retinyl-palmitate hydrolysis in HSCs in humans. Importantly, this indicates a potential novel link between HSCs, retinoid metabolism and PNPLA3 in determining the susceptibility to chronic liver disease.